In situ infrared spectroscopy study of PYR14TFSI ionic liquid stability for Li–O2 battery - Mozhzhukhina, Nataliia (2017)
In situ infrared subtractive normalized Fourier transform infrared spectroscopy (SNIFTIRS) experiments were performed simultaneously with the electrochemical experiments relevant to Li-air battery operation on gold cathodes in ionic liquid PYR14TFSI based electrolyte. Ionic liquid anion was found to be stable, while the cation PYR14 + was found to decompose in studied conditions. In oxygen saturated LiTFSI containing PYR14TFSI electrolyte carbon dioxide and water were formed at potential 4.3 V either with or without previous oxygen electro-reduction reaction. However in deoxygenated LiTFSI contacting ionic liquid no formation of CO2 or water was observed, suggesting oxygen presence to be crucial in carbon dioxide production.